The vision of the Disney World: an experience marketing study at The Walt Disney Company - Patrocínio, Rachel Farias do; Souza, Juliana Lopes de Almeida; Santos, Carolina Toledo Oliveira; Martins, Katheryne Soares (Archives of Business Research, 2018)
The article aims to understand through interviews with Disney park goers and prospects the strategies that the multinational company The Walt Disney Company uses to become a brand that enchants, using the so-called experience marketing. The project also looks at how The Walt Disney Company's strategies can influence not only customers but also prospects to trust and desire the brand. The survey pointed out that more than 90% of visitors had their expectations surpassed, even though they had a high level of expectation of knowing the parks.